Conceptions of ethical competence in relation to action readiness in Education for Sustainable Development. Issue 2 (4th March 2017) - Grice, Marie; Franck, Olof
Abstract: This paper explores notions of ethical competence in relation to Education for Sustainable Development (ESD). It carves out a conceptual field for future empirical research, by coupling the promotion of action readiness as an empirical concept with a theoretical understanding of ethical competence. The concept of competence displays interpretative pluralism as a concrete attribute of an individual or task and an unattainable ideal beyond the specific. With interpretive care, ethical competence, with its origin in values education, is suggested as a foundation of action readiness as ESD competence. In educational practice, action readiness is assumed to be fostered through real-world learning opportunities.